FDI into Kazakhstan : A comparative analysis of EU and Chinese investments. - Alkenov, Dayan; Taušer, Josef; Dissyukov, Almas; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This Master thesis focuses on FDIs impacts from China and EU on Kazakhstan economic development. Comparative analysis includes volume and structure of investments, sectoral division and most importantly strategic implications and nature of investments. Moreover, Kazakhstan specifics of geopolitical positioning and investment landscape were also discussed.
Vedoucí práce: Josef Taušer
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses